Shoreline Change and Coastal Erosion in West Africa: A Systematic Review of Research Progress and Policy Recommendation - Johnson Ankrah; Ana Monteiro; Helena Madureira (Geosciences, 2023)
Shoreline change and coastal erosion resulting from natural events such as sea level rise and negative anthropogenic activities continue to be problems in many of the world’s coastal regions. Many coastal socio-ecological systems have become vulnerable as a result, especially in developing countries with less adaptive capacity. We utilized the systematic method to understand the research progress and policy recommendations on shoreline change and coastal erosion in West Africa. A total of 113 documents were retrieved from Scopus and the Web of Sciences databases, and 43 documents were eligible following established criteria. It was revealed that research on shoreline change and coastal erosion has progressed substantially since 1998, with most research studies originating from the Ghanaian territory. Again, most of the shoreline change and erosion problems in West Africa result from natural events such as sea level rise. However, there was evidence of anthropogenic influences such as sand mining, dam construction, and human encroachment causing shoreline change and erosion in the region. Research in the region has also progressed in terms of methodological approaches. Since 2004, researchers have utilized remote sensing and GIS techniques to source and analyze shoreline change and erosion. However, a combination of remote sensing and field observation approaches is required to clearly depict the erosion problems and aid policy direction. The overall call to action regarding policy recommendations revolves around improving coastal adaptation measures and the resilience of communities, instituting proper coastal zone management plans, and improving shoreline change and coastal erosion research. To protect lives and property, policymakers in the region need to set up good coastal zone management plans, strengthen adaptation measures, and make coastal communities more resistant to possible risks.